Age-related Interrelation of Vibration Perception Thresholds and Somatosensory Evoked Potentials in Normal Subjects - Hirayama, Toyoko; Kaneshige, Yuh; Chiba, Susumu; Kikuchi, Susumu; Noro, Hiroshi; Yanada, Yukiko; Matsumoto, Hiroyuki (Nihon Rōnen Igakkai zasshi, 1990)
In order to establish the age-related changes of vibration perception thresholds (VPTs) and somatosensory evoked potentials (SEPs), which are known to share a common afferent pathyway in the central nervous system, 119 normal subjects ranging in age from the 20s to the 90s were studied. The VPTs of the index fingertip were measured at 63Hz, 125Hz and 250Hz by a Rion vibrometer, nd the latencies of the SEPs to the median nerve stimulation (N9, N13 and N20) were simultaneously evaluated. The VPT, tended to elevate from the 40s, became increased towords higher frequencies (63Hz<125Hz<250Hz) in the 80s to the 90s, whereas the VPT in younger ages showed just an opposite pattern (63Hz>125Hz>250Hz). None of the height-corrected latencies of N9, N13, N20 and central conduction time (N20-N13) revealed a significant correlation between the VPTs at any frequencies. The age-related decline of vibration sense, therefore, could not be explained solely by the degenerative changes of he posterior column and/or the delay of the peripheral nerve conduction velocity. This phenomenon was rather thought to be compatible with an age-associated characteristics of Pacinian corpuscles.